P7C3-A20 treatment one year after TBI in mice repairs the blood-brain barrier, arrests chronic neurodegeneration, and restores cognition - Vázquez-Rosa, Edwin; Shin, Min-Kyoo; Dhar, Matasha; Chaubey, Kalyani; Cintrón-Pérez, Coral J; Tang, Xinmiao; Liao, Xudong; Miller, Emiko; Koh, Yeojung; Barker, Sarah; Franke, Kathryn; Crosby, Danyel R; et al. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Chronic neurodegeneration in survivors of traumatic brain injury (TBI) is a major cause of morbidity, with no effective therapies to mitigate this progressive and debilitating form of nerve cell death. Here, we report that pharmacologic restoration of the blood-brain barrier (BBB), 12 mo after murine TBI, is associated with arrested axonal neurodegeneration and cognitive recovery, benefits that persisted for months after treatment cessation. Recovery was achieved by 30 d of once-daily administration of P7C3-A20, a compound that stabilizes cellular energy levels. Four months after P7C3-A20, electron microscopy revealed full repair of TBI-induced breaks in cortical and hippocampal BBB endothelium. Immunohistochemical staining identified additional benefits of P7C3-A20, including restoration of normal BBB endothelium length, increased brain capillary pericyte density, increased expression of BBB tight junction proteins, reduced brain infiltration of immunoglobulin, and attenuated neuroinflammation. These changes were accompanied by cessation of TBI-induced chronic axonal degeneration. Specificity for P7C3-A20 action on the endothelium was confirmed by protection of cultured human brain microvascular endothelial cells from hydrogen peroxide-induced cell death, as well as preservation of BBB integrity in mice after exposure to toxic levels of lipopolysaccharide. P7C3-A20 also protected mice from BBB degradation after acute TBI. Collectively, our results provide insights into the pathophysiologic mechanisms behind chronic neurodegeneration after TBI, along with a putative treatment strategy. Because TBI increases the risks of other forms of neurodegeneration involving BBB deterioration (e.g., Alzheimer's disease, Parkinson's disease, vascular dementia, chronic traumatic encephalopathy), P7C3-A20 may have widespread clinical utility in the setting of neurodegenerative conditions.